Energy Harvesting and Thermal Management System in Aerospace - Jiang, Fan; Zhao, Shiyu; Wang, Lei; Yu, Shanmeng; Guan, Hongyu; Liu, Jinguo (Frontiers in Materials, 2022)
Thermal management of the spacecraft refers to the adjustment, distribution and comprehensive use of uniform adjustment, allocation, and integrated use of the spacecraft and subsystems, which have the advantages of reducing energy consumption and improving the overall performance of spacecraft. The article is first briefly elaborated on the research progress of thermal management, and then introduces the key thermal control technology of thermal management, mainly thermal bus, heat pump technology and passive thermal control technology. Finally, the future development direction and research focus of thermal management is proposed, which lays a foundation for the future development of thermal management technology.